Estado, direito e politícas públicas: um estudo sobre a incidência normativa na educação superior a partir da Constituição Federal de 1988 - MAGNO, Michelle Feitosa (Universidade Federal do Pará, 2011)
This study has as its main subject the analysis of the public policies drawn up by the Brazilian State through normative regulations for the higher education. Using as categories of analysis the university autonomy and the funding of higher education, the research is based on the premise that public policies have been build from legal regulations. Thus, we searched into the Brazilian State public policies issued by it through legal standards and its consequences in higher education. This study is a bibliographic research that performs a detailed survey of the legal system developed by the Brazilian State for higher education from the Federal Constitution of 1988 until the year 2006. We found out that subsequently to the current Constitution, forty four legal regulations, two of them being constitutional amendments, eleven laws, three interim measures, nine decrees, among others normative standards were approved regarding the university autonomy and funding of higher education, and that also concurred to a profound change in the constitutional text. In the development of the study we started with the argumentation about the State, in order to establish the relations between the Law and the public policies. Then, we draw an historical contextualization of all Brazilian Constitutions, with emphasis on the process of redemocratization started in 1974 and reaching its highest point in the Constitution of 1988, whose key feature was its definition as the most democratic Magna Carta known in Brazil. In this Constitution, we discuss the articles that infer on university autonomy and funding of higher education. Based on the discussion of the Brazilian State and the information provided by the Constitutional Law, we conducted an analysis of post-constitutional legislation that sets policies for Brazilian higher education directed to finance that level of education and university autonomy. Taking as reference the constitutional text, we discourse about the constitutionality control as a legal principle. The study showed that most of the infra-constitutional legal rules regulating Brazilian higher education act contra legem mater, when, for example, proceed against the article 207, interfering on the choice of the university leaders, injuring the ability of the university itself legislate about its own topics, or when disentail provided percentages for the financing of higher education, such as the Revisal Constitutional Amendment n. 1/1994 and Constitutional Amendment n. 10/1996, injuring constitutional principles and representing the interests of the neoliberal capitalist state. The study presents a contribution for the educational public policies field, since it allows reflections on the way that the subjective public law comes to education, assured in the constitutional text, has been systematically and successive denied by governments after the Federal Constitution of 1988 that folow the neoliberal state model.